(untitled) (The Batuk, 2019)
This paper tries to excavate the perceptions, experiences and non/cooperation of curriculum development officers and district education officers in culturally non/responsive pedagogical approaches of private schools in Nepal. This paper tries to decontextualize and culturally non responsive education cannot address the pedagogical and socio cultural requirements of the learners and multicultural societies. This research is oriented to fundamental traits of interpretivism, criticalism and postmodernism so that the varying and complicated features of culture and culturally responsive pedagogy would be met. Therefore, it would be a heuristics of multi-paradigmatic research. In this paper I have explored the views, experiences and perceptions of responsible government officials working in curriculum designing and implementation in making our educational endeavors culturally responsive. I have tried to delve into ’world of duty’ to reveal how result oriented they are. Shifting of responsibilities and lack of professionalism has been found to be the major stumbling blocks.